The opposite prognostic effect of NDUFS1 and NDUFS8 in lung cancer reflects the oncojanus role of mitochondrial complex I - Su, Chia-Yi (Sci Rep, 2016)
A recent surge of research on complex I mitochondrial DNA indicates that complex I disassembly regulated by mutation threshold plays a critical role in tumor progression. However, nuclear DNA (nDNA)-encoded core subunits are still a neglected area for cancer investigation. In this study, respective prognostic contributions of 7 nDNA-encoded core subunits were analyzed by immunohistochemical staining and RNA expression data extracted from public resources. The results showed that NDUFS1 and NDUFS8 had the most significant prognostic power in NSCLC patients among all 7 nDNA-encoded core subunits. Patients with low NDUFS1 or high NDUFS8 IHC and RNA expression levels had poor overall survival. Because of the significant correlation between expressions of 7 nDNA-encoded core subunits, multivariate analysis was performed and identified NDUFS1 and NDUFS8 IHC and RNA expression levels retained their leading prognostic roles. By combining NDFUS1 and NDUFS8 as a panel, the most unfavorable prognostic group had a 14-fold increased risk of poor prognosis than the most favorable prognostic group. In conclusion, the opposite prognostic effect of nDNA-encoded core subunits suggests the oncojanus role of nuclear genes regulating complex I dysfunction. The panel with NDUFS1 and NDUFS8 reflecting tumor metabolism status is a novel prognostic predictor for lung cancer.